Detection of Arbuscular Mycorrhizal Fungi in the Root of Allium fistulosum Grown in the Fumigated Field - Anjar Cahyaningtyas; Devanda Ayu Lidya Permata Putri; Ummi Rosyidah; Zulfa Fatmawati (Acta Solum, 2025)
Soil fumigation is important pre-plantation practices to maximize land productivity. Not only effectively eliminate soil pests and pathogens, but this practice also affecting the beneficial soil microbial community including arbuscular mycorrhizal (AM) fungi. The AM fungal community in the roots of Allium fistulosum were studied. The roots have been collected from fumigated and non-fumigated field. The DNA has been extracted, then the fungal LSU ribosomal RNA gene has been amplified and sequenced. Two and three AM fungal OTUs have been detected from fumigated and non-fumigated field, respectively. Decomposer and pathogenic fungi were detected coexist with the AM fungi, suggesting the resilience of these fungi upon fumigation treatment.